2022
DOI: 10.3346/jkms.2022.37.e281
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in HbA1c According to Blood Glucose Control Status During the First 3 Months After Visiting a Tertiary University Hospital

Abstract: Background We evaluated patients visiting a tertiary university hospital due to a diagnosis of diabetes with a goal of achieving blood glucose control and evaluated blood glucose persistence over 7 years according to the change in blood glucose evident at 3 months after the first visit. Methods Patients treated from 2009 to 2013 were categorized into four groups according to the change in HbA1c levels during the first 3 months of follow-up (Best_group, ≥ 1.6% decrease; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We read with interest the article by Kim et al 1 on the long-term control of diabetes mellitus (DM) after visiting a tertiary university hospital. In this study, patients were categorized into 4 groups based on HbA1c changes at three months; Best (≥ 1.6% decrease), Better (0.5-1.5% reduction), Neutral (≤ 0.4% decrease or ≤ 0.4% increase), and Worst (≥ 0.5% increase).…”
mentioning
confidence: 99%
“…We read with interest the article by Kim et al 1 on the long-term control of diabetes mellitus (DM) after visiting a tertiary university hospital. In this study, patients were categorized into 4 groups based on HbA1c changes at three months; Best (≥ 1.6% decrease), Better (0.5-1.5% reduction), Neutral (≤ 0.4% decrease or ≤ 0.4% increase), and Worst (≥ 0.5% increase).…”
mentioning
confidence: 99%
“…In this issue of the Journal of Korean Medical Science , Kim et al 6 reported that changes in early HbA1c levels after a university hospital visit could predict patient clinical outcomes. In this retrospective study, the authors grouped subjects into four by changes in HbA1c levels during the first 3 months after the initial visit: Best_group, ≥ 1.6% decrease; Better_group, 0.5–1.5% decrease; Neutral_group, ≤ 0.4% decrease or ≤ 0.4% increase; Worse_group, ≥ 0.5% increase.…”
mentioning
confidence: 99%